The German social long-term care insurance - structure and reform options - Melanie Arntz; Ralf Sacchetto; Alexander Spermann; Susanne Steffes; Sarah Widmaier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Regarding social needs in Germany long-term care is an important issue due to an ageing population. Shrinking social networks are leading to a greater need for a public long-term care system. In 1995 the social long-term care insurance was introduced in Germany which is similar in nature to the other social insurances, such as the health care or pension insurance. Long-term care insurance funds are generally linked to health insurance funds. The benefits are financed by virtue of an income-based system where all employees covered by the social security system and their employers have to pay equal contributions on a pay-as-you-go basis. In case of long-term care needs a frail person is assigned to one of three care levels according to his/her severity of need. Benefit recipients living in private households can choose between three kinds of transfers: in-kind transfers, lump-sum transfers and combined transfers whereas the amount of in-kind transfers is higher than the lump-sum transfers in all care levels. Benefit recipients living in nursing homes receive the highest amount of transfers. In recent years some drawbacks of the social long-term care insurance structure turned out to be in need of reform: While health insurance is a fully comprehensive system, long-term care insurance only provides limited cover. Therefore, insurance funds have an incentive to shift some services from health care to long-term care insurance. For instance, there is a low incentive to provide rehabilitation measures in order to lower the care level. Additionally, there is no free competition on the long-term care market because care packages included in the in-kind transfers are negotiated (with respect to services and prices) between insurance funds and professional care providers. Finally, the financial situation of the German social long-term care insurance is tight. While in the first years after introduction the net results of revenues and expenditures were positive they have been negative since 1999 which is due to an increasing number of benefit recipients. Therefore, we discuss several reform options which have been proposed in order to overcome the financial and structural problems. Suggestions for the income side include the introduction of fixed premiums, a fully funded system, a private insurance, or a citizens? insurance. The main problem here is to finance the transition from one system to another system. Some proposals are discussed here. The introduction of individual budgets is the most popular option for the outcome side. A social experiment is under way in order to evaluate the impact of so-called matching transfers.
Keywords: I10; I12; I18; 330